Evaluación del manejo de postcosecha del maíz amarillo duro (Zea mays) en la provincia de Picota - Infante Marina, Gabriela (2003)
The present work is orientated to find ideal parameters · for the. handling post-harvest of the hard-yellow corn (Zea. Mays) ~ The present study understood two stages: The first one was carried out in · the property of the Company: San Fernando CORP. (Buenos Aires· - Picota) and · it embraces the handling of the cultivation and the harvest. During the handling of cultivation of the corn the factors were evaluated that we hinder the handling post-harvest as· the plagues of insects (Spodoptera· frugiperda orcogollero, Heliothis zea. or mazorquero and Diatraea. saccharalis or cañero) and the fungi that cause rotting cob. The crop was realized from the determination of the physiologic maturity; which established using the visual method, this method consists in observing the black cape or black point in the base of the grains of corn, that should constitute 50% of these; was also carried out the chemical method (determination of content of starch); in both cases the physiologic maturity was given around 30% of humidity, starting from which they fixed the day to harvest: 1 O, 15 and 20 days after the physiologic maturity. The second. stage consists of two processes: the drying and the storage. The. Artificial drying was carried out in the Mill Agroindustry’s Mhil S.A.C. (San Hilarión - Bellavista) to temperatures of 70 and 60ºC in an electric dryer, and the natural drying in the fields of the Company San Fernando (Buenos Aires - Picota) on plastic blankets to temperatures that oscillate of 40 - 45ºC. In this process, it was controlled the time of drying and the final humidity of the product. The storage was carried out in the Store of Grains of the Company San Fernando (Picota). Two types storage were effected: in warehouse to temperature and environmental relative humidity and in. camera to temperature of 11 - 13ºC and relative humidity of 50 - 65% to study the effect of the storage type on the quality of the grain of hard yellow corn. let was found that in both storage types it varies the quality as for grain split and to infection for füngi/mycotoxin.